Formulation and Evaluation of Body Scrub Using Walnut Shell Powder - Jaymina Panthaki; Yadav Laxmi Rakesh Bhai; Vaidya Shreya Anand Kumar; Amar M. Raval (Asian Journal of Pharmaceutical Research and Development, 2026)
This project focuses on the formulation and evaluation of a body scrub utilizing walnut shell powder as a natural exfoliating agent. Exfoliation is a crucial aspect of skincare as it removes dead skin cells, improves skin texture, and promotes healthier-looking skin. In this study, an emulsion-based body scrub was prepared using walnut shell powder alongside moisturizing agents, a cream base, and fragrance. Walnut shell powder was selected for its natural abrasive properties, which gently scrub away impurities from the skin surface. The formulated product was evaluated for various physical and cosmetic parameters, including appearance, texture, spreadability, pH, washability, and stability. The results demonstrated that the scrub possessed excellent exfoliating properties, stable physical characteristics, and safe application parameters. This study concludes that walnut shell powder can be successfully and safely incorporated into body scrub formulations for cosmetic use.